snoRNA box C/D levels in leukemia cells in chromosomal abnormalities after irradiation - E. V. Rastorgueva; E. S. Pogodina; E. V. Iurova; E. A. Beloborodov; D. E. Sugak; I. A. Tumozov; Yu. V. Saenko; A. Ni. Fomin (Сибирский онкологический журнал, 2025)
The study objective. This paper reviews the express of C/D box snoRNAs (small nucleolar RNAs) and possibility of their use as biomarkers of radioresistance in chromosomal abnormalities. Material and Methods. The study compared the values of log2FC express of snoRNA C/Dbox in radiosensitive (HL-60) and radioresistant (K562) cell lines with different levels of chromosomal abnormalities. The cells were irradiated with X-ray radiation once at a dose of 4 Gy. The expression of snoRNA C/D was evaluated 1, 4 and 24 hours after irradiation, using new generation sequencing (NGS) MiSeq. Results. Different log2FC values were obtained in HL-60 and K562 cell lines 1 hour, 4 and 24 hours after irradiation. Positive expression of C/D snoRNA prevails in HL-60 throughout the experiment. In K562, the predominance of positive values of C/D snoRNA expression was observed 4 hours after irradiation, and negative values of log2FC were observed 24 hours later. the more anomalies there were in the chromosome, the greater the difference in expression we observed. at the same time, the number of C/D snoRNA changed maximally 24 hours after irradiation in the studied cell lines. We noted a greater number of C/D snoRNAs in the HL-60 cell line, and only 3 expressed C/D snoRNAs in the 15th marker chromosome in K562 out of 16 in HL-60 in the same chromosome. Conclusion. Our study showed a low informative value of using C/D snoRNAs family as markers of radiosensitivity in the presence of chromosomal abnormalities in cancer cells.